Hypothesis: Sarcoidosis is a STAT1-mediated disease - Rosenbaum, James T.; Pasadhika, Sirichai; Crouser, Elliott D.; Choi, Dongseok; Harrington, Christina A.; Lewis, Jinnell A.; Austin, Carrie R.; Diebel, Tessa N.; Vance, Emily E.; Braziel, Rita M.; Smith, Justine R.; Planck, Stephen R. (Clinical immunology (Orlando, Fla.), 2009)
Immunologic pathways involved in sarcoidosis pathogenesis are largely unknown. We hypothesized that patients with sarcoidosis have characteristic mRNA profiles. Microarray analysis of gene expression was done on peripheral blood (12 patients, 12 controls), lung (6 patients, 6 controls) and lymph node (8 patients, 5 controls). Comparing peripheral blood from patients with sarcoidosis to controls, 872 transcripts were upregulated and 1039 were downregulated at > 1.5-fold change and a significant q value. Several transcripts associated with interferon and STAT1 were upregulated. Lung and lymph node analyses also showed dramatic increases in STAT1 and STAT1-regulated chemokines. Granulomas in lymph nodes of patients with sarcoidosis expressed abundant STAT1 and phosphorylated STAT1. STAT1 might play an important role in sarcoidosis. This novel hypothesis unites seemingly disparate observations with regard to sarcoidosis including implication of a casual role for interferons, a suspected infectious trigger, T H1 predominating lymphocytes in bronchoalveolar lavage, and the association with hypercalcemia.